Changes in telomerase activity after irradiation of human peripheral blood mononuclear cells (PBMC) in vitro - Milanović, Dušan; Maier, Patrick; Wenz, Frederik; Herskind, Carsten (Radiation protection dosimetry, 2006)
Telomerase activity (TA) has been shown to be up-regulated by ionising radiation in immortal hematopoietic cell lines. The purpose of the present experiments was to test whether ionising radiation may regulate TA in normal human peripheral blood mononuclear cells (PBMC). A real-time PCR assay was established to quantify TA detected by the telomeric repeat amplification protocol. TA of PBMCs isolated from young healthy donors was highly increased by stimulation with phytohemagglutinin (PHA) for 72 h. Irradiation of PHA-stimulated PBMCs with 2-10 Gy of X rays showed up-regulated TA 4 h after irradiation with an enhancement at least as strong as for the human TK6 lymphoblastoid cell line. The present results show that TA is up-regulated by irradiation not only in immortal cell lines but also in mitogen-stimulated PBMCs. This supports a possible role for telomerase in the cellular radiation response.